Effect of Different Argon Blowing Modes on Refining Effect of Molten Steel - Yang Fengguo, Wang Xiaoying, Zhou Mingxing, Zheng Bing, Xu Dong (Teshugang, 2024)
In this paper， one 180 t double-hole bottom argon blowing ladle is taken as the research object. Based on the specific production conditions， six modes of argon bottom blowing in ladle are numerically simulated， and combined with the field test， it is compared with the argon blowing mode currently adopted. The results show that： （1） The mixing time of molten steel decreases with the increase of argon blowing amount. When argon blowing amount is constant， the argon blowing mode with differential flow rate is stronger than that with constant flow rate. （2） Different modes of argon blowing at the bottom of ladle have different locations and areas of slag holes. When the total flow rate is constant， the maximum velocity of molten steel surface in the differential flow argon blowing mode is greater than that in the constant flow argon blowing mode， which is easy to cause slag entrapment. （3） The fluctuation of slag layer thickness at the slag line in differential flow argon blowing mode is greater than that in constant flow argon blowing mode， and the greater the flow difference， the more severe the fluctuation. （4） The differential flow argon blowing mode further strengthens the refining effect of molten steel by argon blowing at the bottom of ladle through the cooperation of "strong-weak" streams. And the industrial test shows that the number of larger inclusions in steel is obviously more than that in argon blowing mode （400 L/min-600 L/min） with constant flow rate （500 L/min-500 L/min）.